Quarantine, cholera, and international health spaces: Reflections on 19th‐century European sanitary regulations in the time of SARS‐CoV‐2. (27th July 2020) - Pouget, Benoît
Abstract: The current SARS‐CoV‐2 crisis raises questions about the challenges faced by nation states and international organisations in offering a coordinated international response to the pandemic, and reveals the great vulnerability of European countries, which are implementing lockdown measures and imposing restrictions on international travel, for the most part on a unilateral basis. Such measures run counter to the prevailing approach of the previous two centuries that developed an international public health space. This article examines the measures adopted by European states in order to contain 19th‐century cholera pandemics, which took shape through the development of an international maritime quarantine system, based primarily on the implementation of national regulations and local decision‐making. This regime was quickly viewed as ineffective and out of step with liberal ideas that urged a "laissez‐faire" approach to public health matters. In its stead, a long‐term trend developed towards easing quarantine measures. Nation states supported the internationalisation of the fight against pandemics, which chiefly consisted of externalising quarantine measures to the East in order to eliminate them in Europe. This process was based on a subtle dialectical relationship between the construction of an international public health space and the affirmation of state sovereignty, and continued into the 20th century with the progressive creation of international institutions responsible for advancing global health.